NUTRITIVE VALUES OF EIGHT GENOTYPES OF COWPEA WHOLE PLANTS AS FODDER (Journal of Veterinary Medicine and Animal Production, 2021)
The aim of this study was to evaluate eight cowpea genotypes as animal feed, by estimating the chemical composition, dry matter DM and organic matter OM degradability and relative feed value RFV of the whole plant. For degradability study, samples were incubated in rumen for 4,8,16,24,48,72 and 96 hrs using fistulated calves. The experiment was laid out in randomized complete block design with three replicates. Data were analyzed using general linear model. Significant variations (p